Grain bridging locations of monolithic silicon carbide by means of focused ion beam milling technique - Nasiri,NA; Saiz,E; Giuliani,F; Vandeperre,LJ (Materials Letters, 2016)
A slice and view approach using a focused ion beam (FIB) milling technique was employed to investigate grain bridging near the tip of cracks in four silicon carbide (SiC) based materials with different grain boundary chemistries and grain morphologies. Using traditional observations intergranular fracture behaviour and hence clear evidence of grain bridging was found for SiC based materials sintered with oxide additives. More surprisingly, in large grain materials, the FIB technique reveals evidence of grain bridging irrespective of the grain boundary chemistry, i.e. also in materials which macroscopically fail by transgranular failure. This helps to explain why the toughness of large grained materials is higher even if failure is transgranular.